Convective Heat Transfer and Pumping Power Analysis of MWCNT + Fe3O4/Water Hybrid Nanofluid in a Helical Coiled Heat Exchanger with Orthogonal Rib Turbulators - Irandoost Shahrestani, Misagh; Houshfar, Ehsan; Ashjaee, Mehdi; Allahvirdizadeh, Payam (Frontiers in Energy Research, 2021)
Utilizing nanofluids in heat exchangers can lead to improved thermal performance. Nanofluids with suspended carbon nanotubes are specifically desirable in thermal systems because of their unique capabilities. In this study, convective heat transfer and required pumping power are studied simultaneously for a helical coiled heat exchanger with laminar water flow while incorporating 0.1 and 0.3 percent volume fraction of the hybrid nanofluid MWCNT + Fe3O4/water. Two different geometries of bare and ribbed tubes are used for the heat exchanger part. The ribs are chosen to be orthogonal, i.e., 90° with respect to the inclined ones. Three different Reynolds numbers are selected for investigation, all in laminar flow regime based on the non-dimensional M number defined in coiled tubes. Computational fluid dynamics is used to study thermal and fluid behavior of the problem. The convective heat transfer coefficient can serve as a criterion to measure the effectiveness of utilizing nanofluids in heat exchangers by taking the pressure drop and pumping power of the system into consideration. Finally, the artificial neural network curve fitting tool of MATLAB is used to make a good fit in the data range of the problem. It is shown that for most cases of the study, the pumping power ratio is less than 1 that can be considered appropriate from energy consumption viewpoint.